ANALISIS PRODUKTIVITAS DAN PENDAPATAN USAHATANI SAWI (Brassica juncea L.) DI KELURAHAN GUNTUNG PAYUNG KECAMATAN LANDASAN ULIN KOTA BANJARBARU - Suratman, Yan Yozef Agus (Chlorophyl, 2021)
This study aims: (i) to obtain a description of how to plant mustard; (ii) to find out how big the cost of explicit, revenue, and income of mustard farming in the village of Guntung Payung Landasan Ulin Subdistrict. The method used in this research is survey method with observation technique, where sampling technique (sample) is done by simple random sampling from 80 households is taken 38%, so that obtained by 30 respondents. The results showed that the average yield of mustard was 2,590,50 bunch / respondent or 647,63 kg / respondent, the average explicit cost Rp 2,056,471.58 / respondent, the average revenue Rp 9.066.750,00 / responder and income average Rp 7.010.278,42 respondent